Factors that contribute to the effectiveness of Perodua customer retention program / Norfa'izah Safaruddin - Safaruddin, Norfa'izah (Faculty of Business and Management, 2007)
As market growth slows or as markets become more competitive and level of switching costs increase, firms are more likely to attempt to maintain their market share by focusing on retaining current customers. Customer retention has been advocated as an easier and more reliable source of superior performance. This research utilized a convenience methodology to improve customer retention, and the researcher has helped the firm identifying the factors that contribute to retain customer and initiate a variety of strategies to accomplish this objective. Three factors that contribute to retain customer that had been identify by researcher consists of commitment, service quality and long-term relationship. The findings highlight that all the three factors do contribute to retain customer and the firm should take action and focus more on these three contribution factors in order to retain and keep their customers loyal. The researcher also had come out with few recommendations. The recommendations can be taken into consideration. By implementing these recommendations, the researcher optimism that it will help the firm to better upgrade its performance and any area that is not running well in their management for future use.